Mental Health Screening in Juvenile Justice Settings: Evaluating the Utility of the Massachusetts Youth Screening Instrument, Version 2. (October 2018) - Shulman, Elizabeth P.; Bechtold, Jordan; Kelly, Erin L.; Cauffman, Elizabeth
Allocating limited mental health resources is a challenge for juvenile justice facilities. We evaluated the clinical utility of the Massachusetts Youth Screening Instrument, Version 2 (MAYSI-2)—an instrument designed to aid in this process—in three subsamples of justice-involved youth (ages 14-17): detained girls ( n = 69), detained boys ( n = 130), and incarcerated boys ( n = 373). For perspective, we compared its performance (in the incarcerated subsample) to that of the Youth Self-Report (YSR), a more widely-used screen. The MAYSI-2 subscales were moderately useful for detecting relevant diagnoses, and differences were observed across samples. However, as a general mental health screen, the MAYSI-2 performed well (and comparably to the YSR), correctly classifying 66% to 75% of youth. When used to differentiate youth with any and without any disorder, both instruments were effective. Given the MAYSI-2's practical advantages over the YSR (lower cost, easier administration), it may be a better option for juvenile facilities.